Implementation of telehealth is associated with improved timeliness to kidney transplant waitlist evaluation. (August 2018) - Forbes, Rachel C; Broman, Kristy Kummerow; Johnson, Tommy B; Rybacki, Diane B; Hannah Gillis, Angela E; Hagemann Williams, Margarethe; Shaffer, David; Feurer, Irene D; Hale, Douglas A
Introduction: The United States Department of Veterans Affairs (VA) National Transplant Program has made efforts to improve access by introducing Web-based referrals and telehealth. The aims of this study were to describe the programmatic implementation and evaluate the effectiveness of new technology on the timeliness to kidney transplant evaluation at a VA medical centre. Methods: Between 1 January 2009 and 31 May 2016, 835 patients were approved for evaluation. Monthly data were summarized as: number of applications, median days to evaluation, and median percentage of evaluations that occurred within 30 days. Temporal trends were analysed using non-parametric comparisons of medians between three eras: Pre Web-based submission, Web-based submission, and Web-based submission with videoconference (VC) telehealth. Results: The number of applications did not vary between eras ( p = 0.353). The median time to evaluation and the median percentage of patients with appointments within 30 days improved significantly in the Web-based submission with VC era when compared with the Web-based and Pre Web-based eras (37 vs. 260 and 116 days, respectively, p < 0.001; 100% vs. 8% and 0%, respectively, p < 0.001). Discussion: We have been able to markedly improve the timeliness to kidney transplant waitlist evaluation with the addition of telehealth.